Cardiac Conduction Disorders Due to Acquired or Genetic Causes in Young Adults: A Review of the Current Literature - Cristina Balla; Luca Canovi; Marco Zuin; Luca Di Lenno; Maria L. Berloni; Beatrice de Carolis; Assunta Di Domenico; Elisabetta Tonet; Francesco Vitali; Michele Malagu; Giuseppe Boriani; Matteo Bertini (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Cardiac conduction disorders can manifest in young adults in isolated forms, associated with myocardial diseases or as part of a multiorgan disorder. Underlying causes of cardiac conduction disorders may be genetically determined or acquired. Cardiac conduction disorder in young adults is a complex and often underestimated and underrecognized disease that may need of a multidisciplinary team for the diagnosis, treatment, and long‐term management of these patients. Therefore, it is crucial to raise clinicians' awareness of this condition. In this review, we provide a comprehensive update on the cause, diagnosis, and treatment of young adults with cardiac conduction disorders, also suggesting potential strategies to improve the current clinical management of these patients.